2007
DOI: 10.1016/j.virol.2006.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity between epsilon and phi sequences in pregenomic RNA influences hepatitis B virus replication efficiency

Abstract: Hepatitis B virus (HBV) replication requires the viral polymerase to reverse transcribe the 3.5-kb pregenomic viral RNA within the nucleocapsid. It has been proposed that a sequence element designated phi (phi), which is located 32 nucleotides upstream of the 3' DR1 pregenomic RNA sequence and is complementary to epsilon, is required for efficient minus-strand synthesis because it may mediate the translocation of the viral polymerase plus the three nucleotide primer from epsilon to DR1. A mutation in phi has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…10B). Indeed, it has been reported recently that a sequence element designated phi is complementary to the RNA packaging signal epsilon, and such complementarity is required for efficient minus-strand DNA synthesis, probably related to the TP-protein primer translocation from epsilon to DR1 (55). Similarly, the chaperone activity could contribute to the plus-strand DNA synthesis by affecting the DNA-RNA base pairing at the step of RNA primer translocation to DR2 (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…10B). Indeed, it has been reported recently that a sequence element designated phi is complementary to the RNA packaging signal epsilon, and such complementarity is required for efficient minus-strand DNA synthesis, probably related to the TP-protein primer translocation from epsilon to DR1 (55). Similarly, the chaperone activity could contribute to the plus-strand DNA synthesis by affecting the DNA-RNA base pairing at the step of RNA primer translocation to DR2 (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Nucleic acid chaperone activity has been detected in the nucleocapsid proteins of several other viruses (20,24,27,32,55). These earlier studies with different viruses on the nucleic acid chaperone hypothesis in the literature can perhaps be extended to hepatitis B virus, as was discussed in the study of the arginine clusters of the carboxy-terminal domain of HBc (63).…”
Section: Figmentioning
confidence: 90%
“…More recently, we (1) and others (13) demonstrated that the 5Ј half of the upper stem of ε base pairs with another sequence, , which is near the 3Ј end of pgRNA, to make an important contribution to the synthesis of minus-strand DNA.…”
mentioning
confidence: 92%
“…Previous studies showed that base pairing between the adjacent portion of and the 5Ј half of the upper stem of ε was important for function (1,13). Thus, appears to act as a scaffold by base pairing with two regions: and the 5Ј half of the upper stem of ε.…”
mentioning
confidence: 99%
See 1 more Smart Citation